دراسة تأثير اضافة السليكا على الخصائص الفزيائية لطين البنتونايت العراقي - مهدي, شذى هاشم (Al-Nahrain Journal of Science, 2018)
Ceramic samples of bentonite as the base material are obtained by adding a finite amount of SiO2. The prepared samples are standing for temperature up to 1300ºC, The best ceramic samples treated at (1300) ºC is C4. Tables of the apparent porosity (A.P) presented, it decreases with increasing firing temperature and the lowest value for the sample that contains 75% of bentonite at temperature (1300) ºC.